KOMUNIKASI POLITIK TIM PEMENANGAN UNTUK ABDUL WAHID DAN SF HARIYANTO DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR PROVINSI RIAU TAHUN 2024 - Isrul, Pauzia Latifa; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Political communication is very important in every political process, especially during election campaigns. Through political communication, candidates and their campaign teams convey ideas, visions, missions, and work programs to the public as potential voters. The main objective is to build public understanding, create a positive image, and gain political support for the candidates. This study aims to analyze how the elements of political communication—communicator, communicant, message, and media— influence Generation Z’s voting decisions in the 2024 Riau Gubernatorial Election. This research uses a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. The study applies Political Communication Theory, Uses and Gratifications Theory, and Agenda Setting Theory as analytical frameworks. Informants consist of academics, members of the campaign team, and Generation Z voters in Pekanbaru City. The results show that political communicators, such as the candidates and religious figures (notably Ustaz Abdul Somad), play a significant role in shaping public trust and attracting young voters’ sympathy. The political messages emphasized themes of change and social justice, presented in simple and inspiring ways that were easily accepted by Generation Z as the communicants. Meanwhile, social media platforms such as TikTok, Instagram, and YouTube served as the primary channels for disseminating political messages effectively, aligning with Generation Z’s digital communication habits. Keywords: Communicator, Communicant, Political Message, Social Media